Effect of biochar on yield of taro foliage and germination of erythrina and mulberry trees : - Bouaravong, Bounmay (Can Tho University, 2017)
A series of experiments was carried out to determine the effct of: (i) Biochar and biodigester effluent on yield of Taro (Colacasia esculenta) foliage; (ii) Biochar and partial peeling of stems on soil fertility and germination of Erythrina Variegata cuttings; and (iii) Biochar and peeling of the stake on germination of mulberry (Morus alba).